Pengaruh Nilai, Kualitas Pelayanan dan Komitmen Organisasi Terhadap Kepuasan Pelanggan Pada PT. Asuransi Kresna Mitra Tbk Cabang Palembang - Siti Komariah Hildayanti; Luis Marnisah; Eko Surya Dinata (Universitas Indo Global Mandiri)
Abstract This study aims to analyze the influence of customer value, service quality, and organizational commitment to customer satisfaction PT. Asuransi Kresna Mitra Tbk Palembang Branch. This research is quantitative descriptive. The method used is a survey method. Data analysis techniques are carried out by regression analysis to analyze the hypothesis by showing the nature of the effect of independent variables on the dependent variable. The results showed that the quality of service to customers influenced positively and significantly on customer satisfaction, with the most dominant indicators being